Multi-element isotope fractionation concepts to characterize the biodegradation of hydrocarbons — from enzymes to the environment. (October 2016) - Vogt, Carsten; Dorer, Conrad; Musat, Florin; Richnow, Hans-Hermann
Graphical abstract: Highlights: Several enzymatic hydrocarbon activation mechanisms can be identified by ME-CSIA. Anaerobic activation reactions are generally linked to high hydrogen fractionation. Benzene transformation mechanisms were elucidated in situ by ME-CSIA. More field studies are needed to verify the concept of ME-CSIA. Abstract : Multi-element compound-specific isotope fractionation (ME-CSIA) has become a state-of-the-art approach for identifying biotransformation reactions. In the last decade, several studies focused on the combined analysis of carbon and hydrogen stable isotopes upon biodegradation of hydrocarbons due to its widespread environmental occurrence as contaminants, often in high concentrations. Most known initial transformation reactions of hydrocarbons have been isotopically characterized in laboratory experiments using model cultures. The data suggest that several of these reactions — especially those occurring under anoxic conditions — can be identified by ME-CSIA, although a number of constraints have been realized which may lead to wrong ME-CSIA data interpretations in field studies. Generally, the applicability of ME-CSIA regarding hydrocarbon biodegradation needs to be corroborated in future field studies.